Development of a Tissue-equivalent Magnetic Resonance Imaging Phantom Using Indigestible Dextrin and Soluble Calcium - Yamashiro, Akihiro; Komatsu, Kazuhiro; Itoh, Youichi; Kobayashi, Masato; Kamiya, Naoki; Ootsuka, Kaoru; Kubota, Noritoshi (Japanese Journal of Radiological Technology, 2013)
In magnetic resonance imaging (MRI), the ideal phantom should have similar T1 and T2 values to those of organs of interest for measuring the change in signal intensity, contrast ratio and contrast noise ratio. There have been several reports to develop such a phantom using materials with limited availability or complex methods. In this study, we have developed a simple phantom using indigestible dextrin and soluble calcium at 1.5-tesla MRI. The T1 and T2 values have been reduced by dissolving indigestible dextrin and soluble calcium in distilled water. The similar T1 and T2 values to those of organs (i.e., kidney cortex, kidney medulla, liver, spleen, pancreas, bone marrow, uterus myometrium, uterus endometrium, uterus cervix, prostate, brain white matter, and brain gray matter) have been obtained by varying the concentration of indigestible dextrin and soluble calcium. This phantom is easy to develop and has a potential to increase the accuracy of MRI phantom experiments.